A study on the records management practices of the administration department of the Manila Bulletin - Soriano, Sarahdie L.; Buenrostro, Iyra S.; Manila Bulletin (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study analyzed the present records management practices of the Administration Department of Manila Bulletin. The existing practices were then compared with the International Standard for Records Management of the ISO-15489-2:2001.
Principal findings showed that although there is no written policy regarding records management, the Administration Department of Manila Bulletin employs strict implementation of the existing standard operating procedures. Also, the current program of the records system does not include indexes. The facilities being utilized by the Department are complete and satisfactory when it comes to proper storage and security. Since the Department follows a schedule when to appropriately dispose records, the space for the record storage is enough. There has also been no training done yet for the personnel involved with recordkeeping.
To further improve the existing policies and practices of the Department, recommendations were given. It will be beneficial for the Department to have properly classified and indexed records. It also facilitates a more efficient way of locating the needed records. Also, there should be a clear written policy regarding records management. The staff should be asked and encouraged to attend seminars and training on records management to make them fully aware of the latest procedures and best practices in records management.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Records -- Management; Newspaper presses -- Philippines -- Manila